(untitled) (International relations and international law Journal, 2016)
The article explores the relevant aspects of termination of the employment contract due to expiry. Despite the expiry of the employment contract, the labor legislation of Republic of Kazakhstan provides for the right of pregnant women to demand extending the contract from the employer. In practice there are often conflict situations arising when renewing an employment contract with pregnant employees. Having analyzed the case of a particular labor dispute, the article’s author in accordance with the labor legislation of Republic of Kazakhstan gives her recommendations and suggestions on this topic.